Exploring the Link Between Cephalosporin Antibiotic Use and Urolithiasis: A Case–Control Study (Asian Journal of Pharmaceutics (AJP), 2024)
Purpose: The study aimed to explore the association between cephalosporin antibiotics and urolithiasis, specificallyfocusing on Oxalobacter formigenes ( O. formigenes) a colonization process. Materials and Methods: Anobservation was made that 50 were among patients, with kidney stones and 110 without stones had participatedin the study. O. formigenes, a bacterium known to metabolize oxalates in the gastrointestinal tract, was detectedin 36 of the 50 kidney stone patients and in 97 of the 110 control participants. Results: It was found that calciumand oxalate levels in urine. There was a significant increase in kidney stone patients than in controls, suggestingthat these elevated levels may contribute to stone formation. Given the sensitivity of O. formigenes to certainantibiotics, including cephalosporins, frequent antibiotic use may reduce O. formigenes. This reduction could leadto increased oxalate absorption, as O. formigenes is not present to metabolize oxalates effectively. Conclusion:Thereby heightening Formation of kidney stones is at risk. According to these findings, the absence or reduction ofspecies colonization may contribute to calcium oxalate stone pathogenesis, especially in patients taking antibioticssuch as cephalosporins. Consequently, this study highlights the need for cautious antibiotic use to preservebeneficial gut microbiota, which assists protecting against diagnosis and treatment of kidney stones. Furtherresearch could confirm these associations and guide antibiotic stewardship practices to prevent disruptions in gutmicrobiome balance that might contribute to urolithiasis.